A CORPUS-BASED STUDY ON ERRORS IN WRITING DESCRIPTIVE TEXT COMMITTED BY SENIOR HIGH SCHOOL STUDENTS IN A MODELLED-SCHOOL CONTEXT WITHIN SIKKA REGENCY, EAST NUSA TENGGARA PROVINCE - De Rosari, Vinsensia Yosefa; Uran, Stefanus Igolois Grenga; Balik, Lusiyana Marieta (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2024)
This case study aims to identify the types and causes of errors often made by students in writing descriptive texts and to provide solutions to reduce errors in writing. This study employs the five stages of error analysis proposed by Ellis and Barkhuzein. Data were collected through observation, written tests, and interviews and were analyzed using qualitative and quantitative approaches. The corpus under inquiry consisted of 50 students’ descriptive writing texts from two classes. The most identified error was the linguistic errors in writing related to second language usage errors. A lack of vocabulary mastery and L1 interference generally cause errors in writing made by students. After the error evaluation stage, the authors recommend the implementation of Continuous Writing Activities and Process Writing Strategies to help students improve their ability to write in English and reduce the errors they make.